2018
DOI: 10.1002/ente.201800572
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation Analysis of Sealed Perovskite Solar Cell with Porous Carbon Electrode at 100 °C for 7000 h

Abstract: Organic‐inorganic CH3NH3PbI3‐based perovskite solar cells have received significant research interest; however, thermal stability issue still remains. Carbon‐based triple‐porous‐layer perovskite solar cells without any hole transporting material were selected in order to investigate the internal degradation process by thermal stresses. The sealed perovskite solar cells at 100 °C showed stable performance in the power conversion efficiency up to 4500 h, but the degradation was accelerated after that. By analyzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…It has been demonstrated that the CG-PSC is the most stable cell architecture with the longest device stability under various stress conditions. 16,13,12 Another advantage of CG-PSC is the ease of upscaling. 17 In a recent report from Fu et al, a non-certified efficiency of 10.09% at AM 1.5 G was achieved in a screen printed small area series interconnected module which had been encapsulated between two glasses using polyurethane hot melt lamination foil.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has been demonstrated that the CG-PSC is the most stable cell architecture with the longest device stability under various stress conditions. 16,13,12 Another advantage of CG-PSC is the ease of upscaling. 17 In a recent report from Fu et al, a non-certified efficiency of 10.09% at AM 1.5 G was achieved in a screen printed small area series interconnected module which had been encapsulated between two glasses using polyurethane hot melt lamination foil.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The side‐sealed cells showed high stability. Though the V OC of the over‐sealed device retained 80 % of the initial value, the J SC and FF declined close to half in the first 30 h. As a result, the PCE was degrade to 20 % of the initial value during the 100 °C thermal stress test over 30 h. As opposed to the mentioned, the photovoltaic parameters of side‐sealed device did not deteriorate during the 100 °C thermal test, and the PCE remained almost constant over 1500 h. Next, they underwent the thermal test towards the side‐sealed device during an extended period of 7000 h [64] . Though the sealed device at 100 °C exhibited stable performance in PCE up to 4500 h, after which the degradation was accelerated.…”
Section: Carbon Counter Electrode Materials In Perovskite Solar Cells (Pscs)mentioning
confidence: 95%
“…Whereas the stability of the device fabricated without the interfacial layer (device-1 f ) encountered a deterioration of more than 63.30% displaying a PCE of 2.62% after 1000 hours. This lower deterioration value for the device-1 c compared to that of the device-1 f , could be attributed to the better interfacial contact between EC-GC encapsulated perovskite/ EC-GC based HTM which facilitates hole transfer at the interface and prevents the degradation of perovskite material against air and moisture which resulted in achieving long-term stability 72,84,85 . Hence, all the devices fabricated in the present work consists of an EC-GC10 encapsulated perovskite interfacial layer.…”
Section: Device Stability Test Under Ambient Condition the Previous mentioning
confidence: 97%